Laser-induced graphene synthesis of Co3O4 in graphene for oxygen electrocatalysis and metal-air batteries. (November 2018) - Ren, Muqing; Zhang, Jibo; Tour, James M.
Abstract: We present here a straightforward synthesis of highly efficient bifunctional OER/ORR catalysts through a facile laser-induced graphene (LIG) process to produce Co3 O4 /LIG. The Co3 O4 /LIG showed OER and ORR activity comparable to noble metal-based catalysts in alkaline electrolyte. Furthermore, the Co3 O4 /LIG exhibited promising performance in Zn-air and Li-O2 batteries. The rechargeable Zn-air battery has an open-circuit potential of 1.46 V and a high power density of 84.2 mW/cm 2 at 100 mA/cm 2 . The Li-O2 battery with the Co3 O4 /LIG cathode exhibits low overpotentials in both charge and discharge processes and excellent cycling stability up to 242 cycles. Graphical abstract: Image 1